Nonlinear optics - Boyd, Robert W., 1948- (Academic Press, 2008)
Nonlinear optics is the study of the interaction of intense laser light with matter. The book introduces the entire field of optical physics and specifically the area of nonlinear optics. It focuses on fundamental issues including the electromagnetic origin of optical phenomena, the quantum mechanical description of the optical properties of matter, the role of spatial symmetries in determining the optical response, causality and Kramers Kronig relations, and ultrafast and high intensity optical effects. The book also covers applied aspects of nonlinear optics such as harmonic generation, the operation of parametric oscillators, optical switching, photonics, materials issues in nonlinear optics, and processes such as laser damage that can restrict the use of nonlinear optics. This edition contains new material on: applications of harmonic generation including applications within the fields of microscopy and biophotonics; electromagnetically-induced transparency; spectroscopy based on coherent anti-Stokes Raman scattering (CARS).--From publisher description.